The role of environmental heterogeneity for the maintenance of distinct bird communities in fragmented forests. (2nd October 2019) - Willrich, Guilherme; Lima, Marcos Robalinho; dos Anjos, Luiz
ABSTRACT: If a forest fragment maintains original heterogeneous habitat conditions after deforestation and fragmentation of the landscape, is it possible that distinct communities can still remain within the forest remnant as they once occurred in the continuous forest landscape? In the present study, we assessed whether a single forest fragment could harbour different bird communities and the potential factors driving this distinction. Bird abundance and composition were compared between two distinct regions within a single large forest fragment, which differ in topography and vegetation physiognomy. The forest fragment was located in southern Brazil and consisted of pristine semi-deciduous forest. Our analysis indicates the occurrence of two different bird communities within the interior area of a single forest fragment. Variation partitioning also indicated that environmental features, particularly bamboo cover and humidity, were the main factors explaining bird species occurrence. We suggest that habitat heterogeneity is important for the maintenance of these bird communities and it leads to: (1) high levels of bird species diversity, and (2) maintenance of important ecological mechanisms (e.g. species sorting) within the forest fragment. Understanding the ecological processes involved in habitat distribution inside single forest fragments is important, yet usually not properly evaluated in forest fragmentation studies. Our results suggest that considering forest fragments as single ecological units can be misleading. We highlight the need to critically evaluate individual features of forest fragments, beside other landscape metrics, in order to identify important forest fragments for biodiversity conservation.